Evaluasi dan Optimalisasi Durasi Pelaksanaan System Test Menggunakan Metode Critical Path Method dengan Software POM-QM di PT. XYZ - , Rafael Adhi Wicaksono; M. Tutuk Safirin (Jurnal Serambi Engineering, 2025)
Project management is a critical element in ensuring the smooth execution of tasks within the planned timeframe, budget and quality. In the maritime industry, one of the major challenges is to manage the complexity of production phases that involve numerous activities and dependencies. This study aims to analyse and optimise the duration of the electrical and electronic outfitting phase in the Type B ship project at PT. XYZ using the Critical Path Method (CPM) supported by the POM-QM for Windows software. The results show that the application of CPM successfully identified the critical activity path, namely A-B-D-F-H, and reduced the project duration from 128 days to 89 days, achieving a time efficiency of 39 days. This optimisation significantly reduces the potential for operational cost overruns without compromising the quality of the work. This study highlights the importance of data-driven project planning to minimise delays and improve resource efficiency. As a recommendation, CPM and supporting tools such as POM-QM can be more widely implemented on similar projects in the maritime industry to improve productivity and overall project sustainability.